Acculturation and Millennial Migration: A Cultural Congruence Framework - Robinson, Alexandra (Canadian Journal of Counselling and Psychotherapy, 2019)
As the world becomes more interconnected the impact of migration and acculturation have become an increasingly relevant topic. This article provides a review of the dominant theories of acculturation, a critique of these theories, and suggested revisions to current models that reflect the millennial context of migration. A revised perspective, the Cultural Congruency Framework, is proposed. A key premise of the framework is that individuals contextually engage in strategies to align their values, beliefs, and behaviours to experience cultural congruence. Suggestions are provided for implementing this framework in the context of counselling psychology.